2018
DOI: 10.1016/j.envpol.2018.01.034
|View full text |Cite
|
Sign up to set email alerts
|

The gains in life expectancy by ambient PM2.5 pollution reductions in localities in Nigeria

Abstract: Global burden of disease estimates reveal that people in Nigeria are living shorter lifespan than the regional or global average life expectancy. Ambient air pollution is a top risk factor responsible for the reduced longevity. But, the magnitude of the loss or the gains in longevity accruing from the pollution reductions, which are capable of driving mitigation interventions in Nigeria, remain unknown. Thus, we estimate the loss, and the gains in longevity resulting from ambient PM pollution reductions at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 53 publications
0
23
1
Order By: Relevance
“…Previous studies valuing the cost of air pollution in Nigeria are also worth noting. For example, Etchie et al estimated the health cost of air pollution in all Nigerian states, based on satellite-derived PM 2.5 data [18]; the result for Lagos State was substantially lower than that of the present study (US$1.1 billion vs. US$2 billion), primarily due to the use of a lower PM 2.5 concentration data and a slightly different methodology. Yaduma et al estimated the economic cost of PM 10 pollution at the national level at US$33.5 billion in 2006 [47], using an earlier methodology [48], not comparable to that employed in the present study [7].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Previous studies valuing the cost of air pollution in Nigeria are also worth noting. For example, Etchie et al estimated the health cost of air pollution in all Nigerian states, based on satellite-derived PM 2.5 data [18]; the result for Lagos State was substantially lower than that of the present study (US$1.1 billion vs. US$2 billion), primarily due to the use of a lower PM 2.5 concentration data and a slightly different methodology. Yaduma et al estimated the economic cost of PM 10 pollution at the national level at US$33.5 billion in 2006 [47], using an earlier methodology [48], not comparable to that employed in the present study [7].…”
Section: Discussioncontrasting
confidence: 79%
“…Figure 1 shows that the PM 2.5 concentration varies from 12 µg/m 3 to 85 µg/m 3 , depending on the location, season, time frame and year of measurement. One publication used satellite data, however without calibration with ground-level measurements [18]. Most other efforts collected PM 2.5 data using air samplers over short periods of time, usually less than three months [19] [24]; and two days a week for one year, from December 2010 to November 2011, in three locations, by [25].…”
Section: Ambient Pm 25 Pollution In Lagosmentioning
confidence: 99%
“…The MR holds a continuous decreasing trend. Existing studies [45][46][47][48] found that pollution has adversely affected the life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Articles represented scientific depth and detail across the continent, covering key public health issues. Among all article types, notable endpoints evaluated were cardiovascular and cardiometabolic outcomes (Wichmann and Voyi, 2012;Benaissa et al, 2016), as well as broader burden of disease or life expectancy estimates (Berhane et al, 2016;Mokdad andGBD 2015 Eastern Mediterranean Region Lower Respiratory Infections Collaborators, 2018;Etchie et al, 2018). Some studies reported null findings.…”
Section: Health Outcomesmentioning
confidence: 99%